I am trying to see why

$\big(\partial_{xx} + \partial_{yy}\big) u(r, \theta) = u_{rr} + \frac{1}{r}u_r + \frac{1}{r^2}u_{\theta\theta}$

I first use the chain rule to say that:

$\frac{\partial u}{\partial x} = u_r r_x + u_{\theta} \theta_x$

And then I calculate:

$r_x = \frac{x}{\sqrt{x^2 + y^2}} = \frac{rcos\theta}{r} = cos\theta$

$\theta_x = \frac{-y}{x^2+y^2} = \frac{-rsin\theta}{r^2} = \frac{-sin\theta}{r}$

Plugging in gives

$\frac{\partial u}{\partial x} = u_r cos\theta - u_{\theta} \frac{sin\theta}{r}$

But I am unsure of how to take the next $x$ derivative and I am wondering if someone can help?


Let's start with $$ \begin{cases} x=r\cos(\theta)\\ y=r\sin(\theta). \end{cases} $$

We compute first $u_r:$ $$ u_r=u_xx_r+u_yy_r=\cos\theta u_x+\sin\theta u_y. $$

$$ u_{rr}=\cos\theta u_{xr}+\sin\theta u_{yr}=\cos\theta (u_{xx}x_r+u_{xy}y_r)+sin\theta(u_{xy}x_r +u_{yy}y_r)=\\ =\cos^2\theta u_{xx}+2\cos\theta\sin\theta u_{xy}+\sin^2\theta u_{yy}. $$


$$ u_\theta=u_x x_\theta+u_yy_\theta=-r\sin\theta u_x+r\cos\theta u_y. $$ So $$ u_{\theta\theta}=-r(\cos\theta u_x+\sin\theta u_y)+r^2(\sin^2\theta u_{xx}-2\cos\theta\sin\theta u_{xy}+\cos^2\theta u_{yy}). $$

Dividing both sides by $r^2$, adding $u_{\theta\theta}$ and $u_{rr}$, and rearraging term we obtain: $$ \Delta u=u_{rr}+\frac 1{r^2} u_{\theta\theta}+\frac 1r u_r $$

A bit of calculation omitted at the end, feel free to ask if something is unclear or wrong.


Use the chain rule again on the functions $u_r, u_\theta, r_x, \theta_x$ (and product rule on the products):

$u_{xx}=(u_{rr}r_x+u_{r\theta}\theta_x)r_x+u_r(r_{xr}r_x+r_{x\theta}\theta_x)+(u_{\theta r}r_x+u_{\theta\theta}\theta_x)\theta_x+u_\theta(\theta_{xr}r_x+\theta_{x\theta}\theta_x)$.

I get:


Likewise for the $u_{yy}$'s you get (using $r_y=\sin\theta, \theta_y=\frac{\cos\theta}{r}$):



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.